Patients with manifest hepatic encephalopathy can reveal impaired thermal perception. (28th January 2015) - Brenner, M.; Butz, M.; May, E. S.; Kahlbrock, N.; Kircheis, G.; Häussinger, D.; Schnitzler, A.
<x xml:space="preserve">Abstract</x> Objectives Previous evoked potential studies indicated central impairments of somatosensory function in patients suffering from hepatic encephalopathy (HE). The aim of this study was to quantify the somatosensory perception in patients with minimal and overt HE. Materials and Methods Forty‐two patients with liver cirrhosis and HE up to grade 2 and 12 age‐matched healthy controls underwent a comprehensive graduation of HE including the West Haven criteria, the critical flicker frequency (CFF), and neuropsychometric testing. Quantitative sensory testing, standardized by the German Research Network on Neuropathic Pain, was performed on both hands. Results Pain and mechanical detection thresholds were unchanged in HE. Tests of thermal processing revealed that patients with HE of grade 2 perceive cold at lower temperatures (cold detection threshold) and need a higher temperature difference to distinguish between warm and cold (thermal sensory limen). These impairments correlated with the CFF. A correction for attention deficits by performing partial correlations using neuropsychometric test results canceled these correlations. Conclusions The present findings demonstrate an impairment of temperature perception in HE. The extent of this impairment correlates with HE severity as quantified by the CFF. The attenuation of the correlations after correction for attention deficits suggests a strong role of attention deficits for the impaired thermal perception. Thus, it provides initial evidence for a central impairment of thermal processing in HE due to alterations in high‐level processes rather than due to peripheral neuropathic processes, which are a frequent complication in patients with liver cirrhosis.